The Manik Angkeran Story-Based Punctuation Board as a Learning Media for Enhancing Students’ Reading Skills for Elementary School - Ni Made Nadia Savita Astin Pramesti; Maria Goreti Rini Kristiatari; Anak Agung Ayu Dewi Sutyaningsih (MIMBAR PGSD Undiksha, 2024)
The rapid advancement of technology has not been fully integrated into the elementary school learning process, particularly in developing students' writing skills in Bahasa Indonesia. One of the challenges encountered is students' low understanding of punctuation use, which affects the quality of their written work. This study aims to analyze the effectiveness of a punctuation board media based on the Manik Angkeran story in enhancing elementary school students' writing skills. This is a development study employing the ADDIE model. The research subjects included one content expert, one media expert, one classroom teacher, and 26 third-grade elementary school students. Data were collected through questionnaires, writing skill tests, and documentation, then analyzed using descriptive quantitative analysis and inferential statistical tests (t-test). The results indicated that the developed learning media fell into the very good category and proved to be effective. The effectiveness of the media was confirmed through the t-test result with a value of tcount 15.504 > ttable 2.060 at a 5% significance level, indicating a significant difference between students' pretest and posttest writing skills scores. In conclusion, the punctuation board media based on the Manik Angkeran story is effective in improving the writing skills of elementary school students. Its implication suggests that this media can serve as an innovative alternative in teaching Bahasa Indonesia, particularly in making punctuation learning enjoyable and meaningful.